2017
DOI: 10.1128/aac.01362-17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of the Pseudomonas aeruginosa MvfR Quorum-Sensing System Interferes with Biofilm Formation and Potentiates Antibiotic-Mediated Biofilm Disruption

Abstract: Pseudomonas aeruginosa biofilms contribute to its survival on biotic and abiotic surfaces and represent a major clinical threat due to their high tolerance to antibiotics. Therefore, the discovery of antibiofilm agents may hold great promise. We show that pharmacological inhibition of the P. aeruginosa quorum-sensing regulator MvfR (PqsR) using a benzamide-benzimidazole compound interferes with biofilm formation and potentiates biofilm sensitivity to antibiotics. Such a strategy could have great potential agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 27 publications
1
53
0
2
Order By: Relevance
“…In the case of P. aeruginosa, candidates include bromo-furanones, patulin, penicillic acid, ajoene, mBTL, and benzamide-benzimidazole (Brackman and Coenye, 2015;O'Loughlin et al, 2013;Starkey et al, 2014). Inhibition of quorum sensing has been shown to induce a dispersion of P. aeruginosa biofilms (Hentzer et al, 2003) and increase sensitivity to aminoglycosides in in vivo P. aeruginosa experiments (Christensen et al, 2012;Maura and Rahme, 2017). However, current QSIs target downstream regulators as opposed to the central regulators of quorum sensing, which likely accounts for their mild to moderate efficacy (Manefield et al, 2002).…”
Section: Pathogen Portraits Of Tolerance Escherichia Colimentioning
confidence: 99%
“…In the case of P. aeruginosa, candidates include bromo-furanones, patulin, penicillic acid, ajoene, mBTL, and benzamide-benzimidazole (Brackman and Coenye, 2015;O'Loughlin et al, 2013;Starkey et al, 2014). Inhibition of quorum sensing has been shown to induce a dispersion of P. aeruginosa biofilms (Hentzer et al, 2003) and increase sensitivity to aminoglycosides in in vivo P. aeruginosa experiments (Christensen et al, 2012;Maura and Rahme, 2017). However, current QSIs target downstream regulators as opposed to the central regulators of quorum sensing, which likely accounts for their mild to moderate efficacy (Manefield et al, 2002).…”
Section: Pathogen Portraits Of Tolerance Escherichia Colimentioning
confidence: 99%
“…In our assays P. aeruginosa PAO1 produced a more robust biofilm than S. marcescens MG1. Many studies show that P. aeruginosa PAO1 is a good biofilm producer (Lee & Zhang, ; Maura & Rahme, ; Rasamiravaka et al., ; Shrout, Tolker‐Nielsen, Givskov, & Parsek, ). In addition, Labbate et al.…”
Section: Resultsmentioning
confidence: 99%
“…In our assays P. aeruginosa PAO1 produced a more robust biofilm than S. marcescens MG1. Many studies show that P. aeruginosa PAO1 is a good biofilm producer (Lee & Zhang, 2015;Maura & Rahme, 2017;Rasamiravaka et al, 2015;Shrout, Tolker-Nielsen, Givskov, & Parsek, 2011). In addition, Labbate et al (2004) found that S. marcescens MG1 biofilm is formed solely by filamentous cells when grown for 24 hr, reaching maturity at 72 hr.…”
Section: Biofilm Formation (Bf) By S Marcescens Mg1 and P Aeruginosmentioning
confidence: 99%
“…1). These compounds also perturb biofilm formation and can potentiate antibiotic-mediated biofilm disruption (48). Rahme went on to describe compounds that can inhibit PqsBC enzyme activity (i.e., the synthetic machinery responsible for the two MvfR-activating ligands HHQ and PQS [ Fig.…”
Section: How? Design Principles For Signals Network and Inhibitorsmentioning
confidence: 99%